2019
DOI: 10.1021/acs.orglett.9b00446
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Control in Positional-Selective C–H Alkenylation of Isoxazoles and a Ruthenium-Mediated Assembly of Trisubstituted Pyrroles

Abstract: High levels of catalyst control are demonstrated in determining the positional selectivity in C–H alkenylation of isoxazoles. A cationic rhodium-mediated, strong-directing group promotes C­(sp 2)-H activation at the proximal aryl ring whereas, the palladium-mediated electrophilic metallation leads to the C­(sp 2)-H activation at the distal position of the directing group. Synthetic elaboration of this C–H alkenylation product via ruthenium and copper co-catalysis leads to an efficient method for the assembly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Kapur and co-workers demonstrated a precise catalyst-controlled selective C–H olefination of isoxazoles 38 . When a cationic rhodium catalyst is used, the transformation was dictated by the cationic nature of the catalyst, and the strong coordination of isoxazole nitrogen led to ortho -C(sp 2 )–H olefination of proximal aryl rings 39 ( Scheme 20 ), 30 while a palladium-catalyst prefers electrophilic C–H activation due to the covalent nature of the catalyst and olefination took place at the distal position of the directing group. The reaction followed an interesting mechanism as KIE studies via both parallel and competitive reactions indicated the absence of the primary kinetic isotope effect highlighting that C–H activation was not the rate limiting step.…”
Section: Proximal C(sp 2 )–H Olefinationmentioning
confidence: 99%
“…Kapur and co-workers demonstrated a precise catalyst-controlled selective C–H olefination of isoxazoles 38 . When a cationic rhodium catalyst is used, the transformation was dictated by the cationic nature of the catalyst, and the strong coordination of isoxazole nitrogen led to ortho -C(sp 2 )–H olefination of proximal aryl rings 39 ( Scheme 20 ), 30 while a palladium-catalyst prefers electrophilic C–H activation due to the covalent nature of the catalyst and olefination took place at the distal position of the directing group. The reaction followed an interesting mechanism as KIE studies via both parallel and competitive reactions indicated the absence of the primary kinetic isotope effect highlighting that C–H activation was not the rate limiting step.…”
Section: Proximal C(sp 2 )–H Olefinationmentioning
confidence: 99%
“…For instance, Kapur reported that exposure of 4-vinylisoxazoles 278 to catalytic RuCl 3 •xH 2 O and stoichiometric Cu(OAc) 2 furnished trisubstituted pyrroles 279. 141 The proposed mechanistic pathway involves activation of the isoxazole nitrogen by the Ru catalyst, enabling ring fragmentation to produce ruthenium-carbene intermediate 280; subsequent 1,5-cyclization then generates the pyrrole ring 279. The role of Cu(OAc) 2 in this transformation is not clearly understood.…”
Section: Isoxazolesmentioning
confidence: 99%
“…Furthermore, the installed C5-alkenylated imidazoles could be subjected to additional alkenylation, affording unsymmetrically substituted benzimidazoles. Recently, Kumar and Kapur developed an interesting catalyst-driven selective C-H functionalization of isoxazoles at the distal and the proximal position as shown in Scheme 24 [49]. The mode of activation in the case of cationic Rh involves the strong coordination with the isoxazole nitrogen, favoring the proximal C-H activation of the arene ring.…”
Section: Scheme 12 Pd-catalyzed C4-olefination Of Oxazolesmentioning
confidence: 99%